Analisis Pengaruh Disiplin Kerja dan Komitmen Kerja Terhadap Prestasi Kerja Karyawan Pada RSUD Kabupaten Bekasi Periode Maret 2023 - Mei 2023 - Lina Sudaryanti; Rakhmat; Slamet (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2023)
This study aims to find out and analyze the work performance of employees / inpatient nurses at Bekasi Regency Hospital in connection with this how employees can work as well as possible and employees have a high work commitment in completing their work with high discipline based on assessments carried out every month. The data collection technique was carried out by distributing questionnaires to 50 employees as samples. The data analysis technique used is multiple linear regression technique which is processed using the help of the Statistical Product and Service Solution (SPSS) computer program. Based on calculations from the SPSS Program, the research results show that work discipline and work commitment have a significant effect on work performance by obtaining the results of the multiple linear regression coefficient analysis, which is Y = 7.483+0.336+0.559 and the results of the t or partial test for the work discipline variable are obtained by the calculated t test. 2.056 < 2.010635 t table, then Ho is rejected and Ha is accepted with a significance value of 0.045 and the results of the t or partial test for the work commitment variable obtained a calculated t test of 3.221 > 2.010635 t table, then Ho is rejected and Ha is accepted with a significance value of 0.002 and the results of the f test or simultaneous calculation of 18.373 > 4.04 F table, then Ho is rejected and Ha is accepted with a significance of 0.000 < 0.05 so it can be interpreted that there is a significant influence between work discipline (X1) and work commitment (X2) together -the same for work performance (Y) at the Bekasi District Hospital.